Age peculiarities of the content of phospholipids in the blood of sterlet - Suleimanova, R.R.; Hudz Ie.А.; Melnychuk D.О.; Kalachniuk, L.H. (Reports of the National Academy of Sciences of Ukraine, 2017)
Comparing the determined content of phospholipids in the blood plasma of sterlet of different ages, it is found that the most total amount of them was in the fish of two years of age compared to three years of age and mature (9 years). Quantitatively, the largest phospholipid fraction — phosphatidylcholine, in sterlet aged 2, 3, and 9 years was: 50.55, 32.43, and 25.53 mg/ml, respectively. While a reduction of other lipid components was negligible in sterlet of three and nine years of age compared to fish aged two years. Therefore, the defined low content of total phospholipids and their components indicates a possible slowing structural recovery of membra nes.